Evaluation of Pralidoxime Use in an Iranian Teaching Referral Hospital - Ali Banagozar Mohammadi; Maryam Zaare Nahandi; Negin Raad; Siroos Javani; Afshin Gharekhani (Pharmaceutical Sciences, 2018)
Background: Organophosphorus (OP) poisonings, a common source of pesticide poisoning, are an important cause of morbidity and mortality in the developing countries. Combination therapy with atropine and oxime is a common practice in the management of OP poisoning. However, the additive benefit of using pralidoxime in addition to atropine remains controversial. Due to inappropriate and widespread use of this relatively expensive and low available antidote, we aimed to evaluate its usage in an Iranian teaching hospital. Methods: Medical files of patients with pesticide poisoning who had been admitted to the poisoning ward between September 2013 and September 2014 were reviewed. Patients with definite diagnosis of OPs poisoning were selected to evaluate rational use of pralidoxime in their treatment regimen. Data were collected using a checklist containing demographic, clinical, and para clinical characteristics, as well as the type of pesticide poisoning. Appropriateness of the pralidoxime therapy was determined based on clinical practice guideline and endorsed by an attending medical toxicologist. Results: 68.8% of patients had been poisoned with insecticides, 27.1% with aluminum phosphide, 2.1% with herbicides, and 2% with rodenticides, respectively. OPs were responsible for 43.8% of all poisoning. All patients with OPs poisoning received pralidoxime after they had been admitted to emergency department, while only 55% of them were eligible to receive pralidoxime. Moreover, pralidoxime had been administered for 59% of patients with non-OPs poisoning, which all of them were clinically inappropriate. Conclusion: The use of pralidoxime in the northwest of Iran is not appropriate and thus, it is highly recommended that a patient-tailored treatment guideline be provided and implemented regionally.